Beyond Freedom of Expression: Nigerian Press and National Interest in Boko Haram Terrorism Coverage - Bukar, Abubakar Alhaji (Indonesian Journal of Counter Terrorism and National Security, 2023)
Boko Haram terrorism which caused the death and displacement of several thousand citizens, as well as the destruction of properties worth billions USD in the Lake Chad countries, has created a general sense of hopelessness in the populace; traumatizing not only Nigerian army but its concerned politicians, among other stakeholders. In this cloud of anxiety and confusion, a respectable Nigerian newspaper, Daily Trust, revealed in a leading front page story that Nigerian army, navy and air force were assembling weapons to launch a massive, collaborative attacks to reclaim some strategic towns from the insurgents. This led to the military invasion of the newspaper’s headquarters and confiscation of some computers. This research therefore analysed the text of the article that led to the invasion; its possible motivation and implications in the war against the insurgency. And aware of the historical adversarial relationship between the press and Nigerian army, the research also sought to find out how the leading national dailies framed the siege in their reportage and commentary. Thus content analysis (both quantitative and qualitative strands) as well as Goffman’s framing theory undergirded the exploration methodologically. Findings from the study revealed that these dailies (and their sources) largely condemned (52.5%) the invasion, with few others justifying it (17.5%). On the other hand, citing evidences from the text of the controversial story, the research extrapolates that such a story provides unintended intelligence to the terrorists who, capitalizing on the credibility of the sources, they leverage to ambush the military combatants or political office holders with precision. The story in question albeit most conspicuous and daring in revelation, is not an exception in the Nigerian press coverage of Boko Haram insurgency. This is, arguably, resorted to for economic expediency – an attempt at “product differentiation” with scoop which occasionally leads to a goof. Both the report and the military reaction to it, it is further argued, portend some danger to public safety and democracy, and projects the two institutions as working at cross-purposes. Thus the research recommends caution in framing stories in such circumstances so as not to provide the much needed ‘oxygen’ for the sustenance of terrorism. Collaboration among institutions and training in conflict-sensitive journalism for reporters and editors can facilitate the process of peace and resettlement of displaced communities, inter alia.